The Effect of Nucleation on DI-Water Based Phase Change Material for Cool Thermal Energy Storage. Issue 1 (April 2021) - Sundaram, P.; Harisudhan, T.; Pavithran, K.
Abstract: This report addresses the study on nucleating effects of DI – water based phase change material by adding salt hydrate like a Sodium chloride, Magnesium chloride and Calcium chloride. DI-water is selected as base PCM in which nucleating agents are added in concentration of 0.3, 0.6 and 0.9 Wt.% to study the solidification characteristics of the PCM. The samples are prepared with the help of magnetic stirring and ultra-sonification process which ensures that the nucleating agents are completely dissolved in the base PCM. An experimental trail is carried out with surrounding heat transfer fluid temperature of -7°C and the solidification history is generated for all PCM samples. From the observation it can be concluded that NaCl 0.9 Wt.%, MgCl2 0.6 Wt.% and CaCl2 0.6 Wt.% shows a significant reduction of supercooling degree. Only NaCl of 0.9 Wt.% shows a reduction of 91.32% in supercooling degree with least increase of 6.73% in solidification time. Thus, Phase change materials proves to be effective in eliminating the discrepancy between demand and supply during peak hour by storing energy during non-peak hours and retrieving when demanded. Thus, it can be used to reduce power consumption during peak hour's demand and reduce the effects on environment.